Reactive oxidant species induced by antifungal drugs: identity, origins, functions, and connection to stress-induced cell death - Gonzalez-Jimenez, Irene; Perlin, David S.; Shor, Erika (Frontiers in Cellular and Infection Microbiology, 2023)
Reactive oxidant species (ROS) are unstable, highly reactive molecules that are produced by cells either as byproducts of metabolism or synthesized by specialized enzymes. ROS can be detrimental, e.g., by damaging cellular macromolecules, or beneficial, e.g., by participating in signaling. An increasing body of evidence shows that various fungal species, including both yeasts and molds, increase ROS production upon exposure to the antifungal drugs currently used in the clinic: azoles, polyenes, and echinocandins. However, the implications of these findings are still largely unclear due to gaps in knowledge regarding the chemical nature, molecular origins, and functional consequences of these ROS. Because the detection of ROS in fungal cells has largely relied on fluorescent probes that lack specificity, the chemical nature of the ROS is not known, and it may vary depending on the specific fungus-drug combination. In several instances, the origin of antifungal drug-induced ROS has been identified as the mitochondria, but further experiments are necessary to strengthen this conclusion and to investigate other potential cellular ROS sources, such as the ER, peroxisomes, and ROS-producing enzymes. With respect to the function of the ROS, several studies have shown that they contribute to the drugs’ fungicidal activities and may be part of drug-induced programmed cell death (PCD). However, whether these “pro-death” ROS are a primary consequence of the antifungal mechanism of action or a secondary consequence of drug-induced PCD remains unclear. Finally, several recent studies have raised the possibility that ROS induction can serve an adaptive role, promoting antifungal drug tolerance and the evolution of drug resistance. Filling these gaps in knowledge will reveal a new aspect of fungal biology and may identify new ways to potentiate antifungal drug activity or prevent the evolution of antifungal drug resistance.